BIOLOGICAL AGENT INNOVATION AS AN EFFORT TO IMPROVE THE ECONOMY OF FARMERS IN MOJOLEGI VILLAGE, GADING DISTRICT, PROBOLINGGO REGENCY - Achmad Febrianto; Ana Sri Wulandari; Sitti Nur Aini (Universitas Nurul Jadid, 2023)
Abstract :The application of biological agent innovation as an effort to improve the agricultural economy in Mojolegi Village, Gading District, Probolinggo Regency is a new breakthrough that started in August 2015. Farmers have started implementing it. Biological agents, this application is one way for farmers to overcome the expensiveness of synthetic fertilizers and also to prevent the bad effects that synthetic chemicals will cause. The negative impacts that will occur on yields and agricultural land due to excessive use of synthetic pesticides in the long term. This biological agent was first applied by Mr. Gatot Suprianto, then invited several people to participate in implementing innovation and creativity with this biological agent. As a pioneer or initial bridge that brought biological age innovation to Mojolegi Village, he did not want what he got after becoming a representative for the production of biological agents which was carried out by the Probolinggo central agricultural sector in 2015 to not be realized well. This activity succeeded in attracting the attention and interest of other farmers to follow how to make and apply these biological agents. From the research in Mojolegi Village, 3 results were obtained, namely: The Influence of Biological Agent Innovation on the Economy of Farmers in Mojolegi Village, Application and Innovation of Biological Agents in Mojolegi Village, Mojolegi Village Farmers' Views on the Beginning of Biological Agent Innovation